Building Batik Craftsmen Learning Society (Design Case) - Nurwandi, Luthfi; Abdulhak, Ishak; Sumantri, Endang; S Ardiwinata, Jajat (International Journal of Engineering and Technology, 2018)
This research was based on construction of the learning society in the face of global competition for batik craftsmen in small and medium enterprises (SME's) industrial sector of batik in Indonesia. Formation of the learning society was important to do, so that the important work of batik design experienced no piracy and extinct both from the design side as well as craftsmen. With regard to the phenomenon the purpose of the research is finding important the determinant factors in order to shaping the learning society, which becomes the container for batik craftsmen to get recognition of batik designs, as well as the competence of the profession. There were three factors that affect the formation of the learning society for batik craftsmen namely adult learning in an era of competition, the adultâ€™s performance in the era of competition and universal design. In this study, the influence of these three factors that affect the learning society would be observed. The results of this research show that batik craftsmen build their knowledge and skill to form their performance before, construct learning society, while another batik craftsmen used their expertise to form their performance before construct learning society.Â Â